Percepção de agricultores familiares na adaptação do sistema de cultivo de corte e trituração - OLIVEIRA, Carlos Douglas de Sousa (2002)
The difficult that small farmers have to obtain tecnologies generated from institutions of the science and tecnology is related with the difficult that researchers have to include the small farmers in their researches but that is not the main problem. The principal problem is the absent from the projects which trouble about to articulate with the cognitive system from small farmers. In this research it was searched to interprete the perception from small farmers on the system of the cultivation from the slash-andmulch proposed by SHIFT project in the northeast of Pará State. Several experiments were accomplised to compare slash-and-burn and slash-and-mulch system at beginning of the perception of the small farmers. It was focussed mainly the management of the work and control from invadeness in the cleared land prepared. The datas more relevant from research were obtained across the attendence of the prepare of the cleared land from the six small farmers. In this moment we can know the tradicional knowledge used in the slash-burn-system. So can appraise that slash and mulch does not present components which unpracticable its articulation with the tradicional knowledge.